The Effect Of Giving Social Rewards And Recognition On The Independence Of Children Aged 4-5 At Tk Adhyaksa 23 Mataram - Mulyan, Andi; Musda, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study is to get reliable information regarding the impact of social rewards and attitudes on the well-being of children aged four to five years old who are enrolled in the TK Adhyaksa 23 Mataram.